The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1111/vsu.12484
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Abstracts Presented at the American College of Veterinary Surgeon Annual Meetings (2001–2008) and Their Subsequent Full‐Text Publication

Abstract: ACVS abstracts were promptly and reliably published, but final full-text publications often differed substantially from the original abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(69 citation statements)
references
References 48 publications
4
62
3
Order By: Relevance
“…Furthermore, PRPs play an important role in promotion of authors working in academia, and a lesser role in the promotion of those working in private practice. Thus, it is not surprising that, similar to our results, many studies have shown significantly higher publication rates by authors working in universities . However, it is also possible that author affiliation had an effect on other variables, as we did not analyze interaction between variables.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, PRPs play an important role in promotion of authors working in academia, and a lesser role in the promotion of those working in private practice. Thus, it is not surprising that, similar to our results, many studies have shown significantly higher publication rates by authors working in universities . However, it is also possible that author affiliation had an effect on other variables, as we did not analyze interaction between variables.…”
Section: Discussionsupporting
confidence: 87%
“…In ophthalmology meetings, publication rates of 52% and 63% have been reported for the 2010 and 1985 meetings of the Association for Research in Vision and Ophthalmology (ARVO), respectively, and 21% for the 2006 meeting of the American Academy of Optometry . In veterinary medicine, publication rates of 66–73% have been reported for the 2001–2010 meetings of the American College of Veterinary Surgeons (ACVS), and 73.5% and 63% for the 1990–1999 and 2003–2008 meetings, respectively, of the American College of Veterinary Anesthesia and Analgesia (ACVAA) . Thus, it would seem that the 29% publication rate of ECVO meeting abstracts in the years we studied is lower than that of many other biomedical conferences, although it is similar to the 29.6% publication rate of 10 265 abstracts presented at 52 dental conferences …”
Section: Discussionmentioning
confidence: 99%
“…The Vision for Animals Foundation (VAF) Resident grants may be able to address this discrepancy by making future funding to institutions dependent on publication of previously VAF funded projects. Funding has previously been associated with publication for other medical meetings, including the ACVA; however, funding did not affect the likelihood of publication of ACVS abstracts …”
Section: Discussionmentioning
confidence: 95%
“…Other studies have demonstrated differences between the content of abstracts and the final publication . Given publication rates of 29 and 32% for the ECVO and ACVO conferences, care should be taken when applying information from these abstracts to clinical decision making prior to subsequent peer‐reviewed publication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation